SOJA, MILHO E ARROZ NO VERÃƒO, EM ROTAÃ‡ÃƒO COM CROTALÃRIA JÃšNCEA NO OUTONO-INVERNO-PERÃODO DE 1999 A 2001 - Mascarenhas, HipÃ³lito AssunÃ§Ã£o AntÃ´nio; Sakai, Emilio; Tanaka, Roberto Tetsuo; Martins, AntÃ´nio LÃºcio Mello; Wutke, Elaine Bahia; Pires, Regina CÃ©lia de Matos; Carmello, Augusto de Camargo; Bortoletto, Nelson (REVISTA DE AGRICULTURA, 2015)
SOJA, MILHO E ARROZ NO VERÃƒO, EM ROTAÃ‡ÃƒO COM CROTALÃRIA JÃšNCEA NO OUTONO-INVERNO-PERÃODO DE 1999 A 2001